The Moravians during the French and Indian War - Weaver, Glenn (Church history, 1955)
In 1754 the English colonies were concentrated along the Atlantic seaboard and the river valleys leading thereto. To the west of this more-or-less densely populated strip lay a vast wilderness permanently inhabited only by Indians and dotted with the isolated military garrisons and trading posts of the French. Because of conflicting claims and a faulty knowledge of geography, neither England nor France had been successful in convincing the other nation of the validity of her territorial claims. Three wars—King William's (1689–1697), Queen Anne's (1702–1713), and King George's (1744–1748) had been fought in an effort to solve this troublesome question, but in 1754 the problem was much the same as it had been in 1689.